Simple and Rapid Determination of Prednisolone-hemisuccinate and Prednisolone in Biofluid Using Syringe-type Minicolumn Coupled with High-Performance Liquid Chromatography - ISHIKURA, CHIYOJI; KOUNO, YUKIMITSU (Japanese Journal of Hospital Pharmacy, 1997)
The determination of prednisolone-hemisuccinate (PSL-HS) and prednisolone (PSL) were performed using high-performance liquid chromatography (HPLC). PSL-HS and PSL were simultaneously extracted and injected onto a silica gel column with a syringe-type minicolumn packed with diatomaceous earth granules. The extraction-injection solvent used was dichloromethane containing 1% ethanol and the mobile phase solvent for HPLC was water-acetic acidmethanol-dichloromethane-n-hexane (0.2: 0.2: 4: 95.6, v/v). PSL-HS and PSL were detected using an ultraviolet detector set at 250 nm. Linear relationships between the amount of sample and peak height were confirmedfrom 0.1 to 100 μg/ml of homogenate of rat rectum and human serum. When an aliquot of 5 μl of sample was introduced to the syringe-type minicolumn, the detection limits of PSL-HS and PSL were as low as 100 ng/ml with each. The method is simple and accurate and is thus applicable to pharmacology and pharmacokinetic studies.